Criação e modelização de diferentes tipos de rolamentos com o uso do software de modelagem 3D fusion360 - Köhn, André Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The main objetive of this study was to build and create 3D models of different bearings using real data. Using the catalogue provided by the manufacturer, five different kinds of bearings were built, using the 3D Software Fusion360 by Autodesk. In this study, some characteristics and benefits that this program could bring are presented, when compared with similar softwares in the market. The main results of this study are the five guides on how to create the bearings step-by-step. These guides can be useful for creating 3D bearings with Fusion360

O objetivo deste trabalho foi construir e roteirizar modelos de rolamentos a partir de dados reais. Através do catálogo fornecido pela fabricante, foram construídos cinco modelos de rolamentos diferentes, utilizando o software Fusion360 da Autodesk. Também foi feita uma apresentação deste software, demonstrando suas características e vantagens em relação aos demais programas disponíveis no mercado. O principal resultado deste trabalho é a apresentação dos 5 roteiros para construção dos rolamentos, documentos que podem servir de base para reprodução futura destas mesmas peças
Creation and modeling of different types of bearings with the use of fusion360 3D modeling software
Keywords: Rolamentos; Software; Imagem tridimensional; Three-dimensional imaging